Cerebral Malaria in Mouse and Man - Ghazanfari, Nazanin; Mueller, Scott N.; Heath, William R. (Frontiers in Immunology, 2018)
Cerebral malaria (CM) is an acute encephalopathy caused by the malaria parasite Plasmodium falciparum, which develops in a small minority of infected patients and is responsible for the majority of deaths in African children. Despite decades of research on CM, the pathogenic mechanisms are still relatively poorly defined. Nevertheless, many studies in recent years, using a combination of animal models, in vitro cell culture work, and human patients, provide significant insight into the pathologic mechanisms leading to CM. In this review, we summarise recent findings from mouse models and human studies on the pathogenesis of CM, understanding of which may enable development of novel therapeutic approaches.